Methionine metabolism and methyltransferases in the regulation of aging and lifespan extension across species. Issue 6 (28th August 2019) - Parkhitko, Andrey A.; Jouandin, Patrick; Mohr, Stephanie E.; Perrimon, Norbert
Abstract: Methionine restriction (MetR) extends lifespan across different species and exerts beneficial effects on metabolic health and inflammatory responses. In contrast, certain cancer cells exhibit methionine auxotrophy that can be exploited for therapeutic treatment, as decreasing dietary methionine selectively suppresses tumor growth. Thus, MetR represents an intervention that can extend lifespan with a complementary effect of delaying tumor growth. Beyond its function in protein synthesis, methionine feeds into complex metabolic pathways including the methionine cycle, the transsulfuration pathway, and polyamine biosynthesis. Manipulation of each of these branches extends lifespan; however, the interplay between MetR and these branches during regulation of lifespan is not well understood. In addition, a potential mechanism linking the activity of methionine metabolism and lifespan is regulation of production of the methyl donor S ‐adenosylmethionine, which, after transferring its methyl group, is converted to S ‐adenosylhomocysteine. Methylation regulates a wide range of processes, including those thought to be responsible for lifespan extension by MetR. Although the exact mechanisms of lifespan extension by MetR or methionine metabolism reprogramming are unknown, it may act via reducing the rate of translation, modifying gene expression, inducing a hormetic response, modulating autophagy, or inducing mitochondrial function, antioxidant defense, or other metabolic processes. Here, we review the mechanisms of lifespan extension by MetR and different branches of methionine metabolism in different species and the potential for exploiting the regulation of methyltransferases to delay aging. Abstract : A potential mechanism linking the activity of methionine metabolism and lifespan is regulation of production of the methyl donor S ‐adenosylmethionine (SAM), which, after transferring its methyl group, is converted to S ‐adenosylhomocysteine (SAH). Methionine metabolism determines the ratio of SAM/SAH metabolites and affects most of the methylation reactions in the cell, which in turn regulate a wide range of processes including ones that were attributed to be responsible for the lifespan extension by MetR.